Contaminación por desechos sólidos llevados por corrientes marinas a la costa caribeña de Honduras - Cruz., Gustavo A; López, Virna; Sosa, Claudia (Revista de Biología Tropical, 1990)
Large amounts of debris of international origen were found along the inhabited artas of the Mosquitia Coast of Honduras, with ao estimaliao of 123.4 Kg. pcr Km of beach: 91.5 % polymer origen. 7.4% glass botl.Ies and 0.94% aluminium can.s. Plastic pellets in densities of 50 to 200/m2 and petroleum tan in densities of Sn.5 m2, with a estimatcd weight of la la 50 gr/m2. We conclude that this material is carried by tbe Caribbean currents from the Antillas and beyond.